2017
DOI: 10.1038/ncomms15193
|View full text |Cite
|
Sign up to set email alerts
|

A peripheral epigenetic signature of immune system genes is linked to neocortical thickness and memory

Abstract: Increasing age is tightly linked to decreased thickness of the human neocortex. The biological mechanisms that mediate this effect are hitherto unknown. The DNA methylome, as part of the epigenome, contributes significantly to age-related phenotypic changes. Here, we identify an epigenetic signature that is associated with cortical thickness (P=3.86 × 10−8) and memory performance in 533 healthy young adults. The epigenetic effect on cortical thickness was replicated in a sample comprising 596 participants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 72 publications
0
24
0
Order By: Relevance
“…A bidirectional communication system exists between the immune system and the CNS. Neuroimmune signaling during the prenatal or early post-natal developmental stages can have long lasting effects on the brain, and is an important determinant of cognitive function and emotional behavior (Dantzer et al, 2008 ; Bilbo et al, 2012 ; Filiano et al, 2017 ; Freytag et al, 2017 ). Peripheral cytokine signaling can modulate astrocytes, microglia and neurons in the CNS (Kohman and Rhodes, 2013 ).…”
Section: Microbiota and The Immune Systemmentioning
confidence: 99%
“…A bidirectional communication system exists between the immune system and the CNS. Neuroimmune signaling during the prenatal or early post-natal developmental stages can have long lasting effects on the brain, and is an important determinant of cognitive function and emotional behavior (Dantzer et al, 2008 ; Bilbo et al, 2012 ; Filiano et al, 2017 ; Freytag et al, 2017 ). Peripheral cytokine signaling can modulate astrocytes, microglia and neurons in the CNS (Kohman and Rhodes, 2013 ).…”
Section: Microbiota and The Immune Systemmentioning
confidence: 99%
“…Crucially, while initial reports have demonstrated that although DNA methylation patterns are largely tissue-specific, often differing between blood and brain [20,21], there are also similarities [22] and blood DNA methylation shows promise as a biomarker for brain-related traits, including neuropsychiatric disorders [23][24][25][26][27], cognitive ability [28,29] and future psychopathology [26]. However, only a few studies of small sample sizes have reported associations between blood DNA methylation and brain phenotypes [26,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…5 No association was found between either EAA measure and cortical thickness. 16 The heterogeneity in these findings reflect the current uncertainty in the field of epigenetic ageing overall. 22 Studies that followed a candidate gene approach focused primarily on SERT (n=13), followed by OXT/R (n=8), FKBP5 (n=7), NR3C1 (n=4), and BDNF (n=4).…”
Section: Approachmentioning
confidence: 99%
“…Six studies included a replication step in an independent cohort and none performed a meta-analysis of multiple cohorts. For instance, Freytag et al 16 performed independent component analysis on 450k DNAm data in blood in a sample of 514 healthy young adults. One of these DNAm components, enriched for processes related to immune function and inflammation, was associated with cortical thickness after correcting for age.…”
Section: Replicationmentioning
confidence: 99%
See 1 more Smart Citation